Especialização em mosquitos-picadores de sapos (Diptera: Corethrellidae): uma perspectiva sob o olhar da ecologia de paisagens - Geisler, Eduardo (Instituto Nacional de Pesquisas da Amazônia - INPA, 2023)
1. Generally, competition excludes pairs of phylogenetically close species across the landscape. Habitat, food and behavior differentiation are some of the factors which facilitate co-occurence between syntopic species. The taxa of frog-biting midges Corethrella are assumed to be specialists on calling male frogs, but little is known about how other ecological gradients and hosts composition influence their distribution and permit their coexistence in continuous landscapes. 2. Our aims were to understand how environmental gradients in habitat, sound frequencies and frog-species composition influence Corethrella species distributions and if habitat and sound frequencies segregate their occurence across a landscape. We also investigated if habitat selection reduces co-occurence between species which share similar acoustic niches. The study was conducted in 20 permanent plots in Central Amazonia using different sound attractants as baits to capture Corethrella species. 3. Habitat-gradients, sound frequencies and frog-species composition all influenced distributions of Corethrella species However, these factors do little to avoid Corethrella co-occurence and habitat selection did not reduce co-occurence of species attracted by the same sound frequencies. These results suggest that competition is unlikely to affect the distribution of adults and that other aspects, such as competition in the larval phase, may be more important to permit their coexistence. 4. The two most abundant species showed strong negative correlations in abundances, potentially indicating competition among these species, but larval habitat specialization is likely to be the most important cause of this pattern.
Specialization in frog-biting midges (Diptera: Corethrellidae): a landscape perspective
Keywords: Ecologia de comunidades